Pelatihan dan Pendampingan Pembuatan Business Model Canvas pada Usaha Konveksi Johor Production Kota Medan - Wisnubroto, Muhammad Parikesit; Yulianto, Kiki (Universitas Padjadjaran, 2025)
Johor Production is one of the companies engaged in the garment industry and supplier of convection products. This company was established in 2018, and has consistently provided a variety of high-quality products. Its products have been trusted by various government agencies, private companies, schools, and specific communities in Medan City, North Sumatra. Over time, more new companies have emerged that operate in similar fields, leading to increased competition and the need for business analysis and development methods in order to maintain their existence. This community service activity aims to assist Johor Production in developing a business model, namely the Business Model Canvas (BMC) to support the company’s growth. The method used in this service includes educational activities through online Zoom meetings for BMC material presentations and direct practice at Johor Production’s production site. During the presentation of the material, the team from Johor Production seemed to pay attention enthusiastically. The discussion and question and answer sessions proceeded smoothly. The direct practice results identified nine (9) BMC elements, each of which is clearly described. These nine elements will be the basis for the development of convection business from Johor Production.Johor Production merupakan salah satu perusahaan yang bergerak di bidang garment industry dan supplier produk konveksi. Perusahaan ini telah berdiri sejak 2018 yang selalu konsisten dalam menghadirkan berbagai produk berkualitas. Produk yang dihasilkan telah dipercayai oleh berbagai instansi pemerintah, swasta, sekolah, hingga komunitas tertentu di Kota Medan, Sumatera Utara. Seiring berjalannya waktu, semakin banyak munculnya perusahaan baru yang bergerak pada bidang serupa. Akibatnya, persaingan akan semakin ketat dan perlunya suatu analisis dan metode pengembangan usaha agar eksistensinya tetap terjaga. Kegiatan pengabdian ini ditujukan untuk membantu dan mendampingi Johor Production dalam menyusun model bisnis, yaitu Business Model Canvas (BMC) agar perusahaan semakin berkembang. Metode yang digunakan dalam pengabdian ini ialah edukasi melalui pemaparan materi BMC secara online dengan Zoom meeting dan praktek langsung di lokasi produksi Johor Production. Selama penyampaian materi, tim dari Johor Production terlihat memperhatikan dengan antusias. Diskusi dan proses tanya jawab berlangsung lancar. Dari hasil praktek langsung di lokasi diperoleh sembilan (9) elemen BMC yang masing-masing diuraikan dengan jelas. Kesembilan elemen ini akan menjadi dasar pengembangan usaha konveksi dari Johor Production.